Usefulness of Timed Up and Go (TUG) Test for Prediction of Adverse Outcomes in Patients Undergoing Thoracolumbar Spine Surgery. Issue 3 (March 2020) - Komodikis, Gregoris; Gannamani, Vedavyas; Neppala, Sivaram; Li, Michael; Merli, Geno J; Harrop, James S
Abstract : BACKGROUND: : Spine surgery rates have increased and the high postoperative morbidity in these patients result in increased costs. Consequently, it is essential to identify patients at risk of adverse outcomes. OBJECTIVE: : To assess whether preoperative Timed Up and Go (TUG) test performance can predict high‐grade postoperative complications. METHODS: : A prospective cohort study of patients undergoing elective thoracolumbar spine surgery in a tertiary care hospital between 2017 and 2018. Patients were assessed preoperatively and assigned to the slow‐TUG group if unable to perform or test performance time was ≥18.4 s. Primary outcome: high‐grade postoperative complications. Secondary outcomes: overall complications, length of stay (LOS), discharge to healthcare facility, readmission and emergency department (ED) presentation. Patients were followed‐up until 6 wk after surgery. RESULTS: : One hundred three patients (mean age 62.95 ± 10.97 yr) were enrolled. Slow‐TUG group were more likely to be classified as American Society of Anaesthesiology (ASA) class 3 (74.1% vs 47.4%, P = .02), non‐independent (25.9% vs 5.3%, P < .01), and frail (92.3% vs 42.1%, P < .01). TUG was an independent predictor of high‐grade complications (adjusted odds ratio (OR): 4.97, 95% CI: 1.18‐22.47), overall complications (OR: 3.77, 95% CI: 1.33‐11.81), discharge to a skilled‐nursing facility (OR: 3.2, 95% CI: 1.00‐10.70), readmission within 6 wk of surgery (OR: 9.14, 95% CI: 2.39‐41.26) and LOS (adjusted incident rate ratio (IRR): 1.45, 95% CI: 1.16‐1.80). CONCLUSION: : Compared to traditional risk factors, TUG is an important predictor of adverse postoperative outcomes and may be used preoperatively to identify high‐risk thoracolumbar surgery patients.